Status of Mission Agreement (SOMA) on the Joint Monitoring Mission in the Nuba Mountains Area of the Sudan (Tufts Archival Research Center, 2005)
This document is an agreement between the Government of the Republic of and the Sudan Peoples' Liberation Movement/Nuba requesting the Friends of Nuba Mountain Group of nations (FNM), as an impartial third party, to organise, equip and establish an international mission, named Joint Monitoring Mission in the Nuba Mountains area of The Sudan.